2017
DOI: 10.1242/bio.026443
|View full text |Cite
|
Sign up to set email alerts
|

Grazing limits natural biological controls of woody encroachment in Inner Mongolia Steppe

Abstract: Woody encroachment in grasslands has become increasingly problematic globally. Grazing by domestic animals can facilitate woody encroachment by reducing competition from herbaceous plants and fire frequency. Herbivorous insects and parasitic plants can each exert forces that result in the natural biological control of encroaching woody plants through reducing seeding of their host woody plants. However, the interplay of grazing and dynamics of herbivorous insects or parasitic plants, and its effects on the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Shrubs were associated with both F1ResRet and F2FunctDiv, and are important components of many Mongolian steppe ecosystems, their presence driven largely by climate and soil texture [61], although some species, such as Caragana microphylla, are associated with heavy grazing [62][63][64]. Many species of shrubs and sub-shrubs are important to pastoral production as protein-rich forage for browsing species (goats, camels) and as fuel for pastoral households.…”
Section: Resultsmentioning
confidence: 99%
“…Shrubs were associated with both F1ResRet and F2FunctDiv, and are important components of many Mongolian steppe ecosystems, their presence driven largely by climate and soil texture [61], although some species, such as Caragana microphylla, are associated with heavy grazing [62][63][64]. Many species of shrubs and sub-shrubs are important to pastoral production as protein-rich forage for browsing species (goats, camels) and as fuel for pastoral households.…”
Section: Resultsmentioning
confidence: 99%
“…The first was that the long‐term grazing exclusion increased plant diversity and plant cover (Good et al., 2013; Zhao et al., 2011) compared with the continuous grazing treatment, resulting in strong interspecific competition. Such strong competition could lead to reduced resource uptake for C. microphylla shrubs, thereby inhibiting their growth, resulting in decreased relative biomass (Guo et al., 2017). Thus, the decrease in sexual allocation, flower numbers, flower weight, fruit set and seed weight, and thereby low sexual reproduction might be due to insufficient nutrition uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, grazing exclusion has been applied in many grasslands to increase herbaceous plant cover and prevent shrub expansion. Studies have shown that grazing exclusion could reduce abundance (Guo et al., 2017; Kirkpatrick & Bridle, 2016; Saatkamp et al., 2018; Xiong et al., 2011; Zhang et al., 2017) and dominance (Good et al., 2013) of shrub plants. However, the mechanism behind this remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fire and overgrazing significantly reduce the aboveground biomass, and livestock grazing preferences may also cause shrubs to become the dominant species of grassland communities. However, grazing also reduces the presence of rodents on grasslands, thus leading to more complex changes in the vegetation composition of grasslands (Calisher et al, 2005;Guo et al, 2017;Valone & Thornhill, 2001). The possible existence of different limiting factors for grasses and shrubs adds complexity to the uncertain conversion between two growth forms.…”
Section: Introductionmentioning
confidence: 99%